Lord of chaos - Jordan, Robert, 1948-2007 (Jordan, Robert, 1948-2007. Wheel of time, 2020)
Rand al'Thor attempts to unite the nations for a last battle with the Dark One. The plan involves a pact with the Aes Sedai, the female mystics of the One Power.